Efektivitas Bimbingan Karir Berbasis Life Skills Teknik Problem Solving Meningkatkan Motivasi Entrepreneurship Santri di Pondok Pesantren Entrepreneur Al-Mawaddah Kudus - Miftahus Sa'adah; Khilman Rofi Azmi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study was to (1) determine the effectiveness of career guidance services based on life skill problem solving techniques to increase entrepreneurship in students; (2) To find out how the entrepreneurship motivation of students after being given career guidance services based on life skills; (3) To find out whether there is an effect of life skill-based career guidance services to increase the entrepreneurship motivation of students; (4) To find out whether life skill-based career guidance services are effective in increasing the entrepreneurship motivation of students. This research is quantitative by reviewing journals and textbooks related to the researched field. This research is quantitative by examining data from sampling by random sample based population at Ponpes Al Mawaddah Kudus. The steps to determine the effectiveness of career guidance for students with five times of treatment and one post test without control group. The phase of this research include: (1) Observation (2) data collection (3) data analysis using an independent sample T Test (t-test) formula using SPSS version 17.0 assistance. The results of data analysis using the Independent Smaple T Test (t-test) formula using the help of SPSS (Statistical Product and Service Solution) version 17 shows that there is an effective life skills-based career guidance to improve student entrepreneurship at Al-Mawaddah Entrepreneur Islamic Boarding School. The increase was obtained by the average data of the control class and the experimental class. The pretest data of the control class showed an average score of 89, the experimental class with an average score of 114 with a difference of 25 and increased in a positive direction.